2020
DOI: 10.1186/s12913-020-05608-5
|View full text |Cite
|
Sign up to set email alerts
|

Certification as support for resilience? Behind the curtains of a certification body — a qualitative study

Abstract: Background: Certification in healthcare often involves independent private sector bodies performing legally required or voluntary external assurance activities. These certification practices are embedded in international standards founded in traditional beliefs about rational and predictable processes for quality and safety improvement. Certification can affect organizational and cultural changes, support collaboration and encourage improvement that may be conducive to resilient performance. This study explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…A very low increase in the overall rating was found in the item -unit change of the quality management (0,132). Although the coefficient is positive, which indicates a certain positive impact, it is very low compared to the findings of other studies, which showed a strong impact of using EFQM models or other best practices of Total Quality Management on organizational performance, even in the longer term (Johannesen et al, 2020;Nabitz et al, 2006;Talib et al, 2011;van Schoten et al, 2016). On the contrary, the negative coefficient has been demonstrated in the comprehensive and systematic management of change (-0.503), which is often underestimated in organizations not only in the health sector but also in other areas.…”
Section: Entrepreneurship and Sustainability Issuescontrasting
confidence: 73%
See 1 more Smart Citation
“…A very low increase in the overall rating was found in the item -unit change of the quality management (0,132). Although the coefficient is positive, which indicates a certain positive impact, it is very low compared to the findings of other studies, which showed a strong impact of using EFQM models or other best practices of Total Quality Management on organizational performance, even in the longer term (Johannesen et al, 2020;Nabitz et al, 2006;Talib et al, 2011;van Schoten et al, 2016). On the contrary, the negative coefficient has been demonstrated in the comprehensive and systematic management of change (-0.503), which is often underestimated in organizations not only in the health sector but also in other areas.…”
Section: Entrepreneurship and Sustainability Issuescontrasting
confidence: 73%
“…Sunol et al (Suñol et al, 2009) demonstrated a positive impact of quality strategies on hospital outputs. Johannesen et al (Johannesen et al, 2020) found that external assessment programs, such as certification, accreditation, may support resilient performance in healthcare by nurturing the potential to respond and learn. Nabitz et al (Nabitz et al, 2006), Van Schoten et al (van Schoten et al, 2016) examined the implementation of the EFQM quality model.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Most studies about regulation address deviation and noncompliance, not how regulatory bodies adapt to challenges in the regulated context and contribute to adaptive capacity (or not) in the regulated organizations (Barber, 2002;Johannesen, 2020;Johannesen et al, 2020). Bearing in mind that the literature lacks studies looking at regulation and resilience, concepts often considered as counterparts, this thesis adds value to the absence in previous research Wiig et al, 2020 b).…”
Section: Summary Of Knowledge Gapsmentioning
confidence: 96%
“…External approaches to quality improvement, such as supervision and regulation, often treat healthcare organizations similarly regardless of size, context, competence, skills, resources, and objectives, which implies a naive outlook on organizations . Moreover, the effects of external inspections in healthcare are unclear, with not much existing knowledge about inspectors' approaches and methods Hovlid et al, 2020 a, b;Johannesen et al, 2020). A recent study did however link the promotion of leadership with external inspection, stressing how external inspection may "boost" the way hospitals manage their internal work of improving quality and patient safety (Husabø et al, 2020).…”
Section: Regulatory Approachesmentioning
confidence: 99%
“…Several authors highlight the value of organizations learning from the practices and experiences of other organizations (Gressgard and Hansen, 2015;Johannesen et al, 2020;Bhaskara and Filimonau, 2021;Fasey et al, 2021;Friday et al, 2021;Habiyaremye, 2021 as central to OL (Khan et al, 2017;Herbane, 2019). This may also spread further, to a whole network, as suppliers interact with each other, thereby also facilitating network resilience (Chen K. D. et al, 2021).…”
Section: Learning From Experiencementioning
confidence: 99%